Meaning: well identified intensions or biological actions? - Stein, Sofia Inês Albornoz (Intuitio, 2012)
Abstract: As Henri Lauener states in “Truth and Reference” (VANDERVEKEN (Org.), Logic, Thought and Action, Springer, 2005), if one wants to determine the truth of a theory, it is necessary to determine the reference and the sense of terms for objects in that theory. Quine, as Lauener interprets it, contradicts himself when he sustains a physicalist realism, from an ontological point of view, and, at the same time, argues for the inscrutability of the reference of terms, as his naturalistic-behavioristic analysis shows. Moreover, Lauener argues that the notion of meaning would be related to the notion of rule, that is to say, intensions and extensions would be “fixed by the totality of the rules which prescribe the correct use of the expressions”. That notion of meaning has, so, according to Lauener, a transcendental status and is opposed to any concept of meaning that could be formulated by a naturalistic perspective. The normativity intrinsic to linguistic activity isn’t, as Lauener states, something that one could describe solely by a naturalistic and extensional discourse. I intend to question the relevance of Lauener’s criticism against the naturalistic point of view in semantics, starting from a distinction between Quine’s naturalistic-behavioristic standpoint and other possible naturalistic standpoints in semantics that wouldn’t exclude the discourse about intensions and intentions. Key words: Logicism; intentionality; naturalism; meaning.